EFFECTIVENESS OF BASKETBALL TRAINING IN DEVELOPING PHYSICAL QUALITIES OF STUDENTS - Arziev, Shinabat Abdirakhmanovich (SCIENCE and SOCIETY, 2026)
This article experimentally examines the effectiveness of basketball training in developing students’ physical fitness. The results demonstrate significant improvements in physical fitness, confirming that basketball training is an effective educational tool for improving students’ physical fitness.